DIGITALIZATION OF MSMEs: IMPLEMENTATION OF PRODUCT DETAIL PAGES AND DIGITAL FINANCIAL MANAGEMENT ON MSMEs IN BOJONEGORO - Riska Nur Rosyidiana; Rizka Miladiah Ervianty; Wahyu Firmandani; Marta Linduwati; Cantika Caesar Margaretha (Jurnal Layanan Masyarakat, 2023)
These recent years Small and Medium Enterprises (MSMEs) undergo a digital transformation in expanding their market reach. Digitalization is applied to all operational activities so that this can be achieved. Digitalization was also carried out by the members of the East Java IKM Forum (FIJ) Bojonegoro Branch. This community service activity, in the form of training and mentoring, aims to expand sales channels through digital marketing and improve business financial management. The number of participants in this community service activity is 25 business actors who are members of FIJ Bojonegoro Branch. Digital marketing optimization is carried out through the implementation of Product Detail Pages. Detailed product information helps business owners to display their products optimally through marketplace applications. In addition, an understanding of financial performance through the preparation of profit and loss statements helps business actors to easily manage working capital so that businesses develop a success. The training activities were delivered in the form of lectures and focus group discussions methods. Meanwhile, mentoring activities are carried out through optimizing product display and preparing financial reports practices. Data were obtained through pre and post-test, question and answer session, and questionnaire survey. The results of the activity show that there was an increase in the skills and knowledge of participants in the field of digital marketing and financial management.